Estimation of Production Technology for Turkish Textile Industry - Dağ, Nesrin (Eastern Mediterranean University (EMU), 2010)
ABSTRACT: This study examines the production technology in Turkish textile manufacturing industry, for the period 1988-2008. It is analyzed whether the production technology can be represented by a cost function or a profit function. A translog cost function is estimated and endogeneity of the output level is analyzed. The estimated translog cost function is also evaluated with hypothesis testing to verify the statistically significance of the independent variables. It is illustrated that the data in Turkish textile industry can be explained by the estimated translog cost function and the output is not an endogeneous variable in textile manufacturing. It is presented that the shares of labor and capital costs are approximately 13.2 % and 2.3 % respectively. It is demonstrated that the contribution of oil price in total cost of input is less than 1 %. Turkish textile industry within the examined period demonstrates an increasing return to scale with a factor of 1.15. Keywords: Production technology, Translog cost function, Textile industry. …………………………………………………………………………………………………………………………………………………………………………………………………………………… Bu çalışma, 1988-2008 yılları arasında Türkiye textil sanayinde üretim teknolojisini araştırmaktadır. Üretim teknolojisinin maliyet fonksiyonu ile mi yoksa kar fonksiyonu ile mi temsil edildiği incelenmiştir. Bir translog maliyet fonksiyonu tahmin edilmiş ve çıktı seviyesinin içsel bir değişken olup olmadığı araştırılmıştır. Tahmin edilen fonksiyon ayrıca varsayım testlerine tabi tutularak, bağımsız değişkenlerin istatistiki önemliliği değerlendirilmiştir. Türkiye tekstil sanayisinin çalışmada tahmin edilen translog maliyet fonksiyonu ile temsil edilebileceği gösterilmiş ve çıktı seviyesinin içsel bir değişken olmadığı bulunmuştur. İşgücü maliyetinin toplam girdi maliyetleri içinde yaklaşık % 13.2, sermaye maliyetinin ise yaklaşık % 2.3 oranında yer tuttuğu görülmüştür. Yakıt maliyetin toplam girdi maliyeti içindeki oranının ise % 1’den az olduğu bulunmuştur. İncelenen zaman aralığında Türkiye tekstil sanayisinin 1.15 oranında ölçeğe göre artan getiri gösterdiği izlenmiştir. Anahtar Kelimeler: Üretim teknolojisi, translog maliyet fonksiyonu, tekstil endüstrisi.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2010. Supervisor: Assoc. Prof. Dr. Mehmet Balcılar.
Keywords: Economics; Textile Industry - Turkey; Production Technology - Translog Cost Function - Textile Industry